2017
DOI: 10.5812/iranjradiol.13937
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging and Proton Magnetic Resonance Spectroscopy Findings in Osteosarcoma Versus Normal Muscle

Abstract: Objectives: The goal of our study was to assess diffusion-weighted (DW) imaging and proton magnetic resonance (MR) spectroscopy findings in osteosarcoma versus normal muscle at 3 Tesla (3 T) MR system. Patients and Methods:Nineteen patients highly suspicious for osteosarcoma and 12 normal young healthy adults were enrolled in this study. Two patients were excluded from the study due to incompatible histopathologic results. DW imaging and multivoxel proton MR spectroscopy at 3 T were performed for all participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The authors demonstrated that visual confirmation of diffusion restriction is sufficient for detecting tumoral tissue without further need for quantification of ADC values. Furthermore, MRS showed a statistically higher maximum Cho/Cr-ratio of OS than of normal muscle, 1.94 ± 1.12 vs. 1.34 ± 0.11, respectively [40].…”
Section: Bone Sarcomasmentioning
confidence: 84%
“…The authors demonstrated that visual confirmation of diffusion restriction is sufficient for detecting tumoral tissue without further need for quantification of ADC values. Furthermore, MRS showed a statistically higher maximum Cho/Cr-ratio of OS than of normal muscle, 1.94 ± 1.12 vs. 1.34 ± 0.11, respectively [40].…”
Section: Bone Sarcomasmentioning
confidence: 84%